Serum uric acid did not affect embryonic and pregnancy outcomes in women without PCOS during IVF procedures - Yan, Niwei; Song, Junli; Jie, Huiying; Lee, Pingyin; Liu, Simin; Yuan, Yuan (Frontiers in Endocrinology, 2024)
Objectives Serum uric acid (UA) levels are associated with many systemic diseases. A previous study confirmed the association between high serum uric acid levels and poor prognosis of in vitro fertilization (IVF) treatment in polycystic ovary syndrome (PCOS) patients. This study aimed to explore the correlation between serum uric acid levels and reproductive outcomes in patients without PCOS. Methods A retrospective study that included 1057 patients who underwent pre-implantation genetic testing for monogenic disorders (PGT-M) treatment from January 2013 to December 2020 was conducted. The study population was further divided into 3 groups according to serum UA levels: the ≤250 μmol/L group, the 251-360 μmol/L group, and the >360 μmol/L group. The controlled ovarian hyperstimulation (COH) treatment outcomes, embryonic treatment outcomes and pregnancy outcomes of the first frozen embryo transfer (FET) cycle were compared among groups. Multivariable linear regression and binary regression were applied to detect the association between IVF outcomes and serum uric acid levels. Results The number of retrieved oocytes, fertilization rate, viable embryo rate, blastocyst formation rate and euploid rate were not associated with serum uric acid levels. The mature oocyte rate was negatively correlated with serum uric acid levels. The pregnancy outcomes of the first FET cycle were also not associated with serum uric acid levels. After adjustment for BMI, the perinatal outcomes were not associated with serum uric acid levels. Conclusion IVF treatment outcomes were not associated with serum uric acid levels in patients without PCOS.